Effects of Sb, Zn doping on structural, electrical and optical properties of SnO2 thin films. (March 2015) - Singh, Rita; Kumar, Manish; Shankar, S.; Singh, Rajeev; Ghosh, Anup K.; Thakur, O.P.; Das, B.
Abstract: Highly transparent, low resistive pure and Sb, Zn doped nanostructured SnO2 thin films have been successfully prepared on glass substrates at 400° C by spray pyrolysis method. Structural, electrical and optical properties of pure and Sb, Zn doped SnO2 thin films are studied in detail. Powder X-ray diffraction confirms the phase purity, increase in crystallinity, size of the grains (90–45 nm), polycrystalline nature and tetragonal rutile structure of thin films. The scanning electron microscopy reveals the continuous change in surface morphology of thin films and size of the grains decrease due to Sb, Zn doping in to SnO2 . The optical transmission spectra of SnO2 films as a function of wavelength confirm that the optical transmission increases with Sb, Zn doping remarkably. The optical band gap of undoped film is found to be 4.27 eV and decreases with Sb, Zn doping to 4.19 eV, 4.07 eV respectively. The results of electrical measurements indicate that the sheet resistance of the deposited films improves with Sb, Zn doping. The Hall measurements confirm that the films are degenerate n-type semiconductors.